Growth of Eucheuma Cottonii Seaweed from Tissue Culture in Pes Fertilizer Solution (Provasoli Enriched Seawater) with Different Dose - Rosyida, Eka; Tobigo, Desiana Trisnawati; Setiana, Setiana (AgriSains, 2019)
Seaweed is one of the coastal resources that has high economic value and is an export commodity of Indonesian fisheries. The problem that is often faced in seaweed cultivation is the availability of quality seeds and available continuously. One effort to meet the needs of seedlings is to apply tissue culture techniques. The purpose of this study was to study and determine the growth of seaweed (Eucheuma cottonii) by giving various doses of PES (Provasol Enriched Seawater). This research was conducted in August to September 2017 at the Network Culture Laboratory, Lombok Aquaculture Fisheries Center (BPBL), Gili Genting Sekotong Barat Hamlet, West Lombok Regency, West Nusa Tenggara Province. The research method was an experiment with 5 treatments of PES fertilizer doses (A: 0 ml; B: 3.5 ml; C: 6 ml; D: 8.5 ml; E: 11 ml) and 4 replications that were designed using a Randomized Complete Design (CRD). Data were analyzed using ANOVA. The results showed the highest specific growth rate, absolute weight and absolute length in treatment D (8.5 ml dose) with a value of 0.030% / week, respectively 0.35 g and 1.41 cm.